Between Speaking and Silence: A Study of Quiet Students - Foster, Charlotte (Journal of International Students, 2012)
Through a precise analysis of written reflections and interviews, Mary M. Reda examines perceptions of speaking and silent students in her book Between Speaking and Silence. Using her first-year composition class for observation, she explores major elements of students’ decisions to speak or be silent frequently depend on teachers, classroom relationships, and students’ senses of identity.